Mechanical properties of metallic composites (Materials engineering (Marcel Dekker, Inc.), 1994)
Covers dispersion-hardened and fibre-reinforced alloys, addressing principal mechanisms, processing and applications. This title deals with mechanical behaviour based on dislocation theory and elastic-plastic mechanics. It provides data on advanced composites are provided.